Cost Effecctive Analysis Of Antibiotic Therapy In Pneumonia Patients At Yogyakarta City Regional General Hospital - Nurul Faizah; Listiana Hidayati; Amrina Amalia Yogananda (Journal Hygeia Public Health, 2026)
Intoduction: Pneumonia is a respiratory disease with high mortality, morbidity, and costs. Antibiotics are the primary treatment for pneumonia. This study aims to evaluate the cost-effectiveness of the single and combination antibiotic therapy in pneumonia patients at RSUD Kota Yogyakarta. Method: Data were obtained from the medical records of patients receiving antibiotic therapy from January to December 2023. The analysis was performed by calculating the Average Cost-Effectiveness Ratio for each therapy regimen. Result and Discussion: The results showed that the single therapy with ceftriaxone inj. was more cost-effective, with an average cost per patient of IDR 4,468,952 and 100% effectiveness, resulting in an ACER value of IDR 44,689.52 per unit of effectiveness. Meanwhile, the combination therapy with Meiact capsules + fosmycin inj. was more cost-effective, with an average cost per patient of IDR 2,832,524 and 100% effectiveness, resulting in an ACER value of IDR 28,325.04 per unit of effectiveness. The combination therapy has a lower cost compared to the single therapy. Conclusion: The conclusion of this study suggests that combination therapy is more cost-effective than single therapy for managing pneumonia patients at RSUD Kota Yogyakarta.